Flow reaction system for the synthesis of benzoylacetonitrile via the reaction of amides and acetonitrile. (23rd November 2022) - Kim, Joonyoung; Park, Myeong Seong; Lee, Sunwoo; Song, Kwang Ho
Graphical abstract: Abstract: Unactivated amides, such as N, N -dimethylbenzamide, react with acetonitrile in the presence of LiHMDS under flow reaction conditions to afford corresponding benzoylacetonitriles in good yields. The sequential flow reaction system is also applicable to the synthesis of benzoylacetonitrile from N -methylbenzamide.